Chemical test and cellular bioactivities and flavor enhancer properties of mung bean protein via glycation reaction - Srisukpachin Nuttakarn; Tabtimmai Lueacha; Sedtananun Saranya; Laohakunjit Natta; Sonklin Chanikan (E3S Web of Conferences)
Mung bean meal is by-product of the vermicelli industry and contains a high protein content of 70 %. Therefore, this research study and development of flavor-enhancers derived from the mung bean meal protein isolated (MPI) reacted with reducing sugars as glucose (Glu) for generating Maillard reaction products (MRPs) under thermal process. Sensory characteristic, antioxidant activities and cellular bioactivities invested under different ratios of MPI:Glu and different reaction times. The optimal production process of MRPs was determined by response surface methodology (RSM) under the desirability criteria. The optimal ratio of MPI:Glu and time for generating high teriyaki odor, savory, DPPH inhibition, ABTS inhibition with low nut odor and bitterness were identified. Results showed that the MPI:Glu ratio of 1.5:1 and reaction time for 150 min (MRP) were the optimum conditions that contributed to the highest teriyaki and savory scores of 2.54 and 2.25, respectively. MRP explored bioactivities, both chemical test and cellular bioactivity. MRP demonstrated both low cytotoxicity and significant anti-inflammatory effects. MRP exhibited non-toxic in Vero cells at 10 mg/mL and it significantly suppressed nitric oxide (NO) release to 18.62 µM with non-toxicity in the murine macrophage; RAW 264.7 at a concentration of 1 mg/mL.